The Effect Of Training, Position Promotion, And Mutation On Employee Performance in PT. Transfashion Indonesia - Nopri Ariansyah; Bayu Airlangga (Journal of World Conference (JWC), 2019)
Quality human resources are needed in obtaining the success of the company. This study aims to determine the effect of training, promotion and mutation on employee performance in Surabaya. The type of research used is quantitative research with a sample of 50 employees of PT. Transfashion Indonesia, which fills out the questionnaire, is all employees. The data analysis technique used is multiple linear regression analysis. The results of the study show that training, promotion and mutation simultaneously influence the performance of employees in Surabaya. As well as training, job promotion and mutations have a partial effect on employee performance in Surabaya. The higher the training, promotion and transfer are, the higher the employee's performance.